Pelatihan Pemanfaatan Limbah Plastik Menjadi Produk Kerajinan Tangan Bernilai Ekonomis di Tim PKK RT 001 RW 008 Dusun Pulau Sialang Kampar - Rahmad Akbar; Dzulhijjah Yetti; Nurbit Nurbit; Harmi Yelm; Indra Habibi; Andri Nofiar Am; Nurkholis Nurkholis; Tri Kurniaty; Santri Utami Ms (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
This training activity on the use of plastic waste into economically valuable handicraft products is a community service program which aims to provide solutions to the problem of managing plastic waste in the community. The main problem faced is the low level of utilization of plastic waste which has the potential to pollute the environment. This training was carried out with the aim that members of the PKK Team RT 001 RW 008 Dusun Pulau Sialang, Kampar, could understand and practice processing plastic waste into handicraft products such as bags, flower vases and home decorations. These products not only have aesthetic value but also economic value, so they can increase people's productivity and financial independence. In addition, this activity is expected to contribute to reducing the volume of plastic waste that ends up in final disposal sites (TPA). Through this training, participants also gain additional knowledge and skills in managing plastic waste, especially used packaging waste such as plastic bags, drink bottles and detergent packaging, into creative and innovative products. Thus, this activity is able to have a positive impact both economically and environmentally for the people of Sialang Island Hamlet.